Performing authenticity: Independent Chinese travellers' tourism dining experiences in Europe. (October 2021) - Cai, Wenjie; Gebbels, Maria; Wan-Zainal-Shukri, Wan Hafiz
Abstract: Authenticity seeking in dining experiences has focused on "perceptions" rather than "doing" and "sense-making". This study aims to understand how independent Chinese travellers perform authenticity through their dining experiences in Europe through the lens of performance theory. A mobile ethnography approach was applied by following 14 informants in 3 trips across Europe to gain an in-depth understanding of independent Chinese travellers' dining experiences. Three sets of field notes, 21 interview transcripts, drawings, reflexive diaries, social media posts, and blogs were collected. The findings suggest that independent Chinese travellers navigate between directed performance and improvised play in tourism dining. They seek the novelties and familiarities of food in the process of perceiving, understanding, appreciating and rejecting authenticity. This study extends our understanding of experienced authenticity through the lens of performance theory. Furthermore, the study provides detailed accounts of overlooked authenticity-seeking through tourism dining of the non-Western market segment. Highlights: Uses performance theory to examine the process of experienced authenticity. Independent Chinese travellers' authenticity seeking through tourism dining. Tourism dining as a form of perceiving authenticity is both "scripted" and "playful". Mobile ethnography offers immersed understandings of mobile individuals.